Trachelomonas (Euglenophyta) from a eutrophic reservoir In Central Mexico - Garduño Solorzano, Gloria (2011)
This study provides valuable information on the ultrastructure and environmental conditions of the Trachelomonas Ehr. (Euglenophyceae) genus in the Guadalupe Dam, a eutrophic reservoir located in the suburbs of Mexico City, which receives a considerable volume of wastewaters. Specimens were collected at surface level between November 2005 and May 2006. Using LM and SEM twelve taxa from phytoplankton were identified of which, 9 are new records for Mexico. The reservoir is warm monomictic, with basic pH values (7.4-10.1), a high concentration of chlorophyll a(18-101 microg l(-1), a permanent anoxic bottom, specific conductivity (K25) of 205 to 290 microS cm(-1), N-NO3, 0.19-1.2 mg l(-1) and P-PO4 0.22-1.6 mg l(-1). Water temperature was 15.6-23.0 degrees C. Most of the Trachelomonas species were found during the dry season, when concentrations of organic matter, nitrogen and phosphorus as well as the temperature were the highest. Higher species richness was also associated with the warmer months. This research contributes to increase our knowledge on Trachelomonas in Mexico and constitutes the first detailed description of lorica ultrastructure of 12 taxa that grow in a body of water with high concentration of nutrients and a moderate amount of mineral contents.